Analytical challenges and technical limitations in assessing circulating miRNAs - Zampetaki, Anna; Mayr, Manuel (Thrombosis and haemostasis, 2012)
MiRNAs are emerging as promising biomarkers in cardiovascular diseases and may constitute a novel mechanism of intercellular communication. Accurate quantification of circulating miRNAs is essential. A variety of technological approaches and platforms have been developed with increased sensitivity and specificity for the detection and quantification of circulating miRNAs. In this review, we focus on the technical aspects and discuss the analytical challenges in profiling circulating miRNAs.